Pengaruh Fraud Hexagon terhadap Kecurangan Laporan Keuangan pada Perusahaan Properti dan Real estate yang Terdaftar di Bursa Efek Indonesia Tahun 2018-2021 - Mirza Aulia Nur Fajri; Gita Berliana Febrianti; Sri Rahmayani (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
This study aims to identify financial statement fraud using the theory of fraud hexagon (financial stability, nature of industry, change in auditors, change of directors, CEO duality and state-owned enterprise). The sampling technique used in this study was purposive sampling. The samples in this study are 8 Property and Real estate companies listed on the Indonesia Stock Exchange in 2018-2021. The analysis technique used in this study is a logistic regression analysis technique using SPSS software version 25. The results of this study, namely financial stability, nature of industry, change in auditor, change of auditor, CEO duality dan state-owned enterprise has no significant effect on the occurrence of fraud in financial statements.